Money Talks to Autocrats, Bullets Whistle to Democrats: Political Influence under Different Regimes - Thea How Choon; Giovanna Marcolongo; Paolo Pinotti (CESifo GmbH, 2024)
Pressure groups may use bribes, violence, or a combination of both to bend politics to their will, and the choice between these methods of influence can vary depending on the type of institutional regime. We empirically investigate the dynamics of bribes and violence around elections in democracies and autocracies using a novel measure of corruption based on the Panama Papers and other massive data leaks on offshore entities in tax havens, which are often used as vehicles for bribes, and data on attacks against politicians around the world between 1990 and 2015. Evidence from staggered difference-in-differences and regression discontinuity in time models shows that in democracies attacks against politicians escalate before elections, whereas in autocracies bribes increase after elections. These findings align with a theoretical framework in which pressure groups use political violence to sway democratic elections in favor of their preferred candidates, while resorting to bribes to influence the behavior of newly appointed bureaucrats and public officials in autocracies.
Keywords: K42; D72; 330; elections; violence; corruption; pressure groups